Factors Impact on Financial Planning Behavior of Upper Secondary School Students in Bangkok - Limsuwanroj , Tananop; Siripanich, Pachitjanut (Business Administration and Management Journal Review, 2021)
The purpose of this research is to study the influence of financial planning behaviour of upper secondary school students in Bangkok. The sample group used in this research was randomized from Two – stage stratified sampling divided into 144 males and 265 females. Statistical analysis was done in terms of percentages, t – test, one - way ANOVA, and stepwise multiple regression analysis. The research results show that the significant factors of the prediction in this study were income of the students from work, financial goals attitude, teaching from parents in investing, teaching from friends in saving, self-learning in investing. These factors were used in the equation of multiple regression analysis.